HUBUNGAN ANTARA KEMAMPUAN ADAPTASI TERHADAP KEBISINGAN DENGAN STRES KERJA KARYAWAN - Asmarani, Ruly (Jurnal Studia Insania, 2017)
Today stress has become a very important management issue in the industrial world. Nearly everyone experiences stress with respect to work. No matter how small the work stress that emerges must be addressed so as not to enlarge which ultimately can harm the organization and employees. One source of work stress is the noise that is not desired by the ear because it can be annoying and irritating. But the noise can be responded differently by each individual according to their adaptability. If the individual is less able to adapt to the noise then he will tend to experience stress.This study aims to determine the relationship between the ability to adapt to noise with employee work stress. This research was designed using a quantitative and correlational approach. Population of this research is employees of production of PT. Hendratna Plywood totaling 357 people. In sampling, the researcher used Random Sampling Technique by taking 60 employees. In this study the researchers used pure try out. The result of try out scale of ability of adaptation to noise obtained 23 valid items from 30 items presented. While on work stress scale obtained 55 valid items from 72 items.The results showed that 32 subjects (53.3%) experienced high work stress and 28 subjects (46.6%) experienced low work stress. It also found that 37 subjects (61.6%) had good adaptability to noise and 23 subjects (38.3%) had poor adaptability to noise. The result of data analysis is known that there is a significant negative relationship between the ability of adaptation to noise with employee work stress shown by correlation coefficient r = - 0,359 and p = 0,005. This means that if employees have good adaptability to noise then low job stress, otherwise if employees have poor adaptability to noise then high job stress. From this it can be seen that the ability of adaptation to noise gives effective contribution of 12,88% (r² = 0,1288) to work stress, while the rest 87,12% influenced by other factor.